Sarcocystis aucheniae (Apicomplexa: Sarcocystidae) infection in muscle tissue of alpacas and llamas in Huancavelica, Peru - Carhuapoma–Delacruz, Víctor; Jurado–Escobar, Melanio; Valencia–Mamani, Nicasio; Castrejón Valdez, Manuel; Sánchez–Araujo, Víctor Guillermo; Capcha–Huamaní, Arnaldo Virgilio; Sánchez–Ramos, Blas Oscar; Esparza, Mario (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Sarcocystis is of clinical importance in public health due to its neurotoxic activity; however, knowledge of the degree of infection in muscle tissues of camelids is limited. In this work, the level of Sarcocystis aucheniae infection in muscle tissue of alpacas and llamas slaughtered for human consumption was evaluated. We considered 969 alpacas and 800 llamas positive to S. aucheniae slaughtered in the Municipal slaughterhouse of Huancavelica, Perú. The detection of Sarcocystis in muscular tissues (neck, rib, diaphragm and inguinal area) was done by direct observation and macroscopic identification and the level of infection by the non–destructive method. S. aucheniae infection was found in alpacas (68%) and llamas (76%), being susceptible in male animals. The level of infection to the parasite was high in the neck (74–85%) and inguinal area (59–68%) in alpacas and llamas, with high frequencies in the neck (58%) and inguinal area (100%) in more than three places of origin, with predominance of infection in the neck (75%), inguinal area (70%) in Suri alpacas and in Chacu llamas (87%), fluctuating frequencies between 60 to 90% in animals with full mouth and four teeth in both species. Alpacas and female llamas presented higher infection in the neck (78–86%) and in males in the inguinal area (60–70%); likewise, there was higher infection in the neck and inguinal area in animals with good body condition and obese (62 to 100%) in both species. A high level of Sarcocystis aucheniae infection was evidenced in the muscle tissue of alpacas and llamas, being susceptible to the parasite in male animals.